2016
DOI: 10.1007/s10730-016-9310-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Moral Case Deliberation Help Professionals in Care for the Homeless in Dealing with Their Dilemmas? A Mixed-Methods Responsive Study

Abstract: Health care professionals often face moral dilemmas. Not dealing constructively with moral dilemmas can cause moral distress and can negatively affect the quality of care. Little research has been documented with methodologies meant to support professionals in care for the homeless in dealing with their dilemmas. Moral case deliberation (MCD) is a method for systematic reflection on moral dilemmas and is increasingly being used as ethics support for professionals in various health-care domains. This study deal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…3,9,10 For instance, in the study of Söderhamn et al, 9 healthcare professionals reported to have experienced an enhanced moral awareness of ethical issues and that they learned more about themselves in order to become better healthcare professionals. More recently, and also with use of a (quantitative) questionnaire, Spijkerboer et al 3 found that MCD fosters working together and fosters communication. Furthermore, a recent literature review reported that impact of MCD was mainly shown at both the individual level and in the relationships between professionals.…”
Section: Experienced MCD Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…3,9,10 For instance, in the study of Söderhamn et al, 9 healthcare professionals reported to have experienced an enhanced moral awareness of ethical issues and that they learned more about themselves in order to become better healthcare professionals. More recently, and also with use of a (quantitative) questionnaire, Spijkerboer et al 3 found that MCD fosters working together and fosters communication. Furthermore, a recent literature review reported that impact of MCD was mainly shown at both the individual level and in the relationships between professionals.…”
Section: Experienced MCD Outcomesmentioning
confidence: 99%
“…1 MCD i has been implemented now for more than two decades in many healthcare settings. [2][3][4][5] MCD is a group dialogue in which professionals (sometimes with patients and family) jointly investigate a moral question that emerges out of a situation they experienced in their daily practice, by reflecting on relevant values and norms from different perspectives and on possible solutions. The dialogue is led by a trained facilitator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dilemmas have their origin in the budgetary cuts of the Welfare State and in the change of social policies because of the economic crisis. These changes generate new ethical tensions in social workers and, apparently, to a greater extent in this area of intervention, as stated in previous studies (Banks, 2011;Spijkerboer, van der Stel, Widdershoven & Molewijk, 2017).…”
Section: Marginalized Homeless Peoplementioning
confidence: 66%
“…These services are organized and managed in regards to the sections of the population at which they are aimed. The following factors are taken into account, without forgetting the previous contributions of other researchers: health (Goldman & Tabak, 2010;Greene & Kulper, 1990;Kadushin, 2001;Proctor, Morrow-Howell & Lott, 1993;Sparks, 2006), childhood (Meysen & Kelly, 2018), immigrants (Furman, Ackerman, Loya, Jones & Egi, 2012;Mänttarivan der Kuip, 2016), women (Cervantes, 1993;Lindhorst, Macy & Nurius, 2005;Wiech, 2009), family (Handon, 2009), homeless (Banks, 2011;Spijkerboer, van der Stel, Widdershoven & Molewijk, 2017), ethnic minorities (Pergert, Ekblad, Enskär & Biörk, 2008;Van Keer, Deschepper, Francke, Huyghens & Bilsen, 2015), youth (Banks, 2012), prisoners (Baldry & Sotiri, 2009;Toi, 2015), the elderly (Bergeron & Gray, 2003;Fitting, 1986;Smebye, Kirkevold & Engedal, 2016), refugees (Barrero, 1993;Hayes & Humphries, 2004), educational centres (Allen-Meares, 2004;Constable, 2002;Dupper, 2003;Openshaw, 2008;Reamer, 2003;Roberts, 1971;Villarreal, 2017), mental health (Molewijk, Hem & Pedersen, 2015), disability (Donat, 2005;Iacono & Murray, 2003;Wilkins, 2012), and drugs …”
Section: Areas Of Social Work Interventionmentioning
confidence: 99%